Mitochondrial Regulation of Microglial Immunometabolism in Alzheimer’s Disease - Fairley, Lauren H.; Wong, Jia Hui; Barron, Anna M. (Frontiers in Immunology, 2021)
Alzheimer’s disease (AD) is an age-associated terminal neurodegenerative disease with no effective treatments. Dysfunction of innate immunity is implicated in the pathogenesis of AD, with genetic studies supporting a causative role in the disease. Microglia, the effector cells of innate immunity in the brain, are highly plastic and perform a diverse range of specialist functions in AD, including phagocytosing and removing toxic aggregates of beta amyloid and tau that drive neurodegeneration. These immune functions require high energy demand, which is regulated by mitochondria. Reflecting this, microglia have been shown to be highly metabolically flexible, reprogramming their mitochondrial function upon inflammatory activation to meet their energy demands. However, AD-associated genetic risk factors and pathology impair microglial metabolic programming, and metabolic derailment has been shown to cause innate immune dysfunction in AD. These findings suggest that immunity and metabolic function are intricately linked processes, and targeting microglial metabolism offers a window of opportunity for therapeutic treatment of AD. Here, we review evidence for the role of metabolic programming in inflammatory functions in AD, and discuss mitochondrial-targeted immunotherapeutics for treatment of the disease.